Walk the blue line [large type] - Patterson, James, 1947-; Eversmann, Matt; Mooney, Chris (Little, Brown and Company, 2023)
"Straight from the mean streets, Walk the Blue Line is a first-person account of the days and nights of America's brave cops"--Dust jacket flap.